The Impact of Green Marketing on Sustainable Development of Community-Based Tourism: Evidence from Pahawang Island, Indonesia - Indriyani, Susi; Novila Sari, Pipit (Graduate School, Universitas Brawijaya, 2026)
Marine-based community tourism depends heavily on effective ecological management, yet the role of the green marketing mix in this context remains insufficiently examined. This study addresses this gap by analyzing survey data from 321 visitors to Pahawang Island Tourism Village, Indonesia. Using multiple linear regression analysis, the findings indicate that green product, attributes, pricing strategies, distribution channels, and promotional activities jointly enhance destination sustainability. The result emphasizes the importance of an integrated green marketing strategy in supporting the triple bottom line, namely, environmental conservation, social well-being, and economic resilience. By capturing supply-side dynamics in a developing-country context, this study offers empirical insights for policymakers and local destination managers to improve sustainable tourism governance.